2017
DOI: 10.1186/s13722-017-0071-3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of health economic models of opioid agonist therapies in maintenance treatment of non-prescription opioid dependence

Abstract: BackgroundOpioid dependence is a chronic condition with substantial health, economic and social costs. The study objective was to conduct a systematic review of published health-economic models of opioid agonist therapy for non-prescription opioid dependence, to review the different modelling approaches identified, and to inform future modelling studies. MethodsLiterature searches were conducted in March 2015 in eight electronic databases, supplemented by hand-searching reference lists and searches on six Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…We identified three systematic reviews evaluating evidence for the economic effectiveness of different opioid use disorder interventions (Chetty et al, 2017;Murphy and Polsky, 2016;Simoens et al, 2006), two of which focused on pharmacological maintenance therapies (Chetty et al, 2017;Simoens et al, 2006). The four HAT source studies discussed in these reviews were all captured by our search strategy.…”
Section: Results For Effects Of Heroin-assisted Treatment On Economicmentioning
confidence: 99%
“…We identified three systematic reviews evaluating evidence for the economic effectiveness of different opioid use disorder interventions (Chetty et al, 2017;Murphy and Polsky, 2016;Simoens et al, 2006), two of which focused on pharmacological maintenance therapies (Chetty et al, 2017;Simoens et al, 2006). The four HAT source studies discussed in these reviews were all captured by our search strategy.…”
Section: Results For Effects Of Heroin-assisted Treatment On Economicmentioning
confidence: 99%
“…We consider the development of the model a step forward in providing researchers a methodology for testing the cost-effectiveness of OST formulations. However, further work is required to develop the model fully, principally due to the limited data in this area 9 . Additionally, future models should include a more comprehensive consideration of the economic and societal consequences (including victim costs) of heroin use 9 .…”
Section: Discussionmentioning
confidence: 99%
“…This may require the development of health economic models. A recent systematic review of economic models that have been used in appraising OST revealed a limited number of models in the peer-reviewed literature, and no clear consensus to modeling approaches 9 . To explore this area further, we replicated an existing health technology assessment (HTA) model developed by Connock et al 10 , and updated the model using 2016 costs.…”
Section: Introductionmentioning
confidence: 99%
“…Most OAT scale‐up modeling studies assume that demand for treatment will always exceed capacity . Individual and structural barriers, however, may restrict demand for OAT in Ukraine .…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization's (WHO) target of 40% coverage of all POUD is ambitious , yet even 20% coverage may be unattainable, regardless of whether or not capacity is increased, due to a lack of demand for OAT by POUD. The typical approach to model the epidemics of substance use disorders (SUDs) and their treatment assumes that an individual's risk of developing SUD and their likelihood of seeking treatment are independent of population‐level drug use prevalence and treatment outcomes . Some researchers argue, however, that drug use may exhibit peer effects, and therefore the drug use initiation rate may exhibit positive density‐dependence , that the demand for treatment may be partly driven by supply and that the dynamics of the waiting‐lists should be taken into account in the assessment of addiction treatment capacity requirements .…”
Section: Introductionmentioning
confidence: 99%